Translation, Cross-Cultural Adaptation, Reproducibility, and Validation: Brazilian Version of the Olerud-Molander Ankle Score (OMAS-BrP) - Castilho, Rodrigo; Silva, Gabriel; Vieira, Cassiano; Tavares, Camilo; Magalhães, João; Zambelli, Roberto (Journal of the Foot & Ankle, 2021)
Objective:The aim of this study was to perform the translation and cultural adaptation of the Olerud-Molander Ankle Score (OMAS) in Brazilian Portuguese, in addition to determining its validity and reliability. Methods: This was a cross-sectional case-series study. The translation and adaptation processes were conducted in 5 stages: initial translation (2 bilingual Brazilians); synthesis of translations; back translation (2 bilingual Brazilians not involved in the first part of the study); consensus version and assessment (technical committee); and testing phase. The test-retest reliability and construct validity of the Brazilian Portuguese version of the OMAS (OMAS BrP) were evaluated in a sample of 40 participants. Construct validity was determined based on the correlations of the OMAS-BrP to the Foot Function Index (FFI) and Short-Form 12 (SF-12). Results: The OMAS-BrP had excellent test-retest reliability (ICC=0.99). The OMAS-BrP showed moderate and weak correlations with the SF 12 PCS and SF-12 MCS (r=0.68 and p<0.001; r=0.38 and p=0.014, respectively). The correlation coefficient between the OMAS-BrP and the FFI was graded as excellent (r=-0.846 and p<0.001). There was a strong correlation between the OMAS-BrP, the SF-12 PCS, and the FFI. Conclusion: The OMAS-BrP is a valid and reliable questionnaire, with psychometric parameters that are similar to those of its original version and other cross cultural adaptations. The OMAS-BrP is a useful patient-reported outcome (PRO) measure to evaluate Brazilian Portuguese-speaking patients with ankle fractures. Level of Evidence IV; Therapeutic Studies; Case Series.